Leitura dos contos de fadas : do escrito ao audiovisual - Santos, Wellinghton (2016)
This TCF presents a proposal to read the wonderful tales from some of the basic stages and functions of this genre, according to the morphology of Propp (2006), making possible the changes of the roles of the classic protagonists and antagonists. Our objective is to perform a subjective re-reading and later rewriting, with the aid of the identification of some narrative stages of the fairy tales, both in the written text and in its adaptation to the audiovisual language. This research was driven by the observation of the reality of literature teaching in elementary school, in which the deficiency is perceived in relation to strategies of literary reading and multiletration in Portuguese language classes. Methodologically, we explore some concepts proposed by Vladimir Propp's studies of the wonderful tale; as regards the issue of literary reading, we apply some aspects of the receptional and semiological methods proposed by Bordini & Aguiar (1988). From the fusion of these two perspectives, we propose a practice of comparative reading of traditional wonderful stories and the re-reading of them in audiovisual adaptations (cinema). In order to do so, we make use of other theoretical contributions of foundation, with particular emphasis to: Campos (2003), Colomer (2007), Coutinho (2006), Cruz (2012), Estés (2005), Gomes (2014), Rojo & Moura 2012), Rouxel (2013), Silva (2006, 2009), Zilberman (1982). This proposal for intervention results in a pedagogical book, with multimodal literary reading workshops, culminating in the production of retellings of fairy tales. From the analysis of the data collection and the results of this research, we suggest a method of literary reading that allows any teacher to use it in their classes, putting the multissemy of the contemporary world and the narrative corpus of wonderful tales in the service of the formation of readers and producers of literary texts.